The Effect of Work Motivation on Improving Teacher Performance in Learning at School - Lubis, Rosida; Rahayu, Nina; Sari, Rita (Mulya Literasi Publishing, 2023)
There are so many tasks and functions performed by teachers in order to develop their noble duties as agents of change. With various problems that must be resolved, teachers are also required to have work targets according to what has been determined. So this paper tries to reveal how motivation affects teacher performance in learning. The writing method uses a qualitative approach with a literature study. The results of the analysis show that work motivation has an influence on teacher performance in schools. If teachers have high work motivation, the quality of teacher performance will also increase it can help teachers in carrying out the teaching and learning process well. Effective work motivation can increase teacher productivity, creativity, and job satisfaction so that the quality of education in schools can also increase. However, it should be noted that there are several other factors that can also affect teacher performance, such as work environment, management support, and personal factors.